2009
DOI: 10.1038/jhg.2009.108
|View full text |Cite
|
Sign up to set email alerts
|

hOGG1 Ser326Cys polymorphism and risk of lung cancer by histological type

Abstract: Human 8-oxoguanine DNA glycosylase 1 (hOGG1) has a major role in the repair of 8-hydroxyguanine, a major promutagenic DNA lesion. The genetic polymorphism rs1052133, which leads to substitution of the amino acid at codon 326 from Ser to Cys, shows functional differences, namely a decrease in enzyme activity in hOGG1-Cys326. Although several studies have investigated the association between rs1052133 and lung cancer susceptibility, the effect of this locus on lung cancer according to histology remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…A previous study by Arizono et al (26) indicated that the frequency of the hOGG1 codon 326 GG genotype was significantly higher in bladder cancer cases compared to the controls. The homozygous GG genotype exhibited a significant association with lung cancer compared to the C allele carrier status in previous studies (27,28). In the present study, individuals who were homozygous for the GG genotype were at a markedly increased risk for developing PCa (OR=2.93; 95% CI: 1-8.74; P=0.033).…”
Section: Discussionsupporting
confidence: 53%
“…A previous study by Arizono et al (26) indicated that the frequency of the hOGG1 codon 326 GG genotype was significantly higher in bladder cancer cases compared to the controls. The homozygous GG genotype exhibited a significant association with lung cancer compared to the C allele carrier status in previous studies (27,28). In the present study, individuals who were homozygous for the GG genotype were at a markedly increased risk for developing PCa (OR=2.93; 95% CI: 1-8.74; P=0.033).…”
Section: Discussionsupporting
confidence: 53%
“…Indeed, OGG1 deficiency has been associated with a mutator phenotype in both yeast and E. coli models Thomas et al, 1997]. Also, as discussed above, inactivating mutations of OGG1, primarily associated with a Ser326Cys mutation, have been described in multiple tumors derived from human samples [Lu et al, 1997;Chevillard et al, 1998;Sugimura et al, 1999;Audebert et al, 2000;Wikman et al, 2000;Audebert et al, 2002;Le Marchand et al, 2002;Paz-Elizur et al, 2003;Farinati et al, 2008;Okasaka et al, 2009]. Interestingly however, investigations in multiple independent OGG1-deficient mouse models have failed to document a strong role for OGG1 deficiency alone on tumorigenesis.…”
Section: Actions Of Ber Glycosylases In Disease States Obesity and Mementioning
confidence: 98%
“…DOI 10.1002/em well as metabolic homeostasis. In this regard, the Ser326Cys mutation has been associated with human lung squamous cell carcinomas [Lu et al, 1997;Chevillard et al, 1998;Sugimura et al, 1999;Wikman et al, 2000;Le Marchand et al, 2002;Paz-Elizur et al, 2003;Okasaka et al, 2009], orolaryngeal [Elahi et al, 2002], esophageal [Xing et al, 2001], kidney [Chevillard et al, 1998;Audebert et al, 2000Audebert et al, , 2002, and gastric cancers [Farinati et al, 2008]. Recently, two studies have also reported an association between the Ser326Cys mutation and increased body mass index and susceptibility to Type II diabetes [Daimon et al, 2009;Thameem et al, 2010].…”
Section: Nth1mentioning
confidence: 99%
“…The risks of explosure to adenocarcinoma of lung and small cell lung cancer were obviously higher among individuals with Cys/Cys genotype than those with Ser/Cys or Ser/Ser (Okasaka et al, 2009). Individuals with Cys/Cys genotype had a higher risk of lung cancer than those with Ser/Cys or Ser/ Ser (Le Marchand et al, 2002).…”
Section: Discussionmentioning
confidence: 99%